Sugar-coated nanoparticles: Investigating lipid-terminated glycopolymers for targeted nanoparticle delivery of nucleic acids - Fiedler, Benjamin (2024)
RNA-based therapeutics are set to transform disease treatment, having already revolutionised our approach to vaccination. However, RNA therapeutics are rapidly degraded by blood enzymes upon administration, do not readily enter cells to their site of action, and do not specifically enter the cell types in which they are biologically active. Targeted nanoparticle drug delivery poses an ideal solution to these issues, however to date, no such system has been clinically approved for RNA therapeutics. Glycosylating nanoparticles to target the endocytic lectin CD206+ is an appealing option due to the expression of CD206+ on attractive targets for nucleic acid delivery (macrophages and dendritic cells), and also the potential for highly specific receptor-ligand targeting. In this body of work, mannose-acrylamide polymers were synthesised via RAFT polymerisation, and investigated as potential CD206 targeting ligands for nucleic acid-loaded nanoparticles. Liposomes, LNPs, and polyplexes were surface functionalised with mannose acrylamide polymers through different surface functionalisation strategies. This study showcases that mannose-functionalised liposomes effectively bind to model mannose-recognising lectin Con A, but their internalisation by CD206+ and CD206- cells was hindered upon surface functionalisation. For LNPs, while internalisation remained similar to PEGylated controls, no mannose-receptor mediated internalisation or cellular association was observed. In contrast, polyplexes displayed specific and significant CD206-mediated internalisation/cellular association. This CD206-mediated internalisation of pDMAEAM-Mannose acrylamide polyplexes was translated into an increased mRNA transfection only when -cholesteryl functionality was incorporated into the polymer architecture at the ω- end of the polymer chain (ω-cholesteryl). ω-cholesteryl polymer functionality was therefore established as a diverse lipid-bilayer inserting moiety. It facilitated successful surface functionalisation of liposomes and LNPs with glycopolymers, opening the door for other polymer chemistries to be investigated on the surface of liposome/lipid nanoparticle. Importantly, ω-cholesteryl also demonstrated its potential for improving mRNA transfection by proving itself critical for improving mRNA transfection of CD206+ targeted polyplexes, through a proposed mechanism of increased endosomal escape through endosome bilayer disruption. Ultimately, this work demonstrates the paramount importance of selecting an appropriate nanoparticle platform during the development of non-viral vectors for nucleic acid delivery. Distinct differences in in vitro results were attributed to the choice of nanoparticle system, despite chemically similar CD206+ targeting units. Moreover, this highlights the success taking a holistic view to designing targeted drug delivery platforms, as success was only achieved when targeted delivery and endosomal escape were simultaneously considered.